God at war : power in the Exodus tradition - Dozeman, Thomas B. (Oxford University Press, 1996)
The destruction of the Egyptian army in the Book of Exodus is the primary story of salvation for Israel; God is the chief combatant in this story. "Yahweh is a warrior!" So goes the victory hymn in Exodus 15:3 after the annihilation of the enemy by Yahweh, marking the importance held by this show of divine power. This unleashing of divine power and its militaristic imagery has long caught the attention of scholars as starkly nationalistic. Thomas B. Dozeman furthers this study by addressing the theological problem of divine power in the Exodus story and, by extension, the Judeo-Chris